Dinanath grass: A potential fodder crop for dryland farming - Sharma, Dimpal; Keerthana, Dhanapati; Dwivedi, Rishika; Singh, Mahendra; Chand, Subhash (Indian Farming, 2026)
Dinanath grass is a fast-growing, high-yielding forage species suited to dryland farming and lowinput systems. Its adaptability to diverse soil types, tolerance to drought, and ability to regenerate after cutting make it a reliable source of green fodder in semi-arid regions. The crop is nutritionally rich, offering 10–12% crude protein, balanced fibre, and essential minerals, which support livestock growth, milk production, and overall health. Dinanath thrives well in warm climates with rainfall between 300–800 mm and grows well on sandy loam soils under full sunlight. It responds well to timely sowing and proper tillage, with a recommended seed rate of 3–4 kg/ha. Improved cultivars such as Bundel Dinanath-2 and Bundel Dinanath-3 offer high biomass yields and disease tolerance. Its compatibility with legumes and cereal intercrops enhances system productivity, profitability, and soil fertility. The inherent resistance of dinanath grass to major biotic and abiotic stresses enhances its adaptability to low-input dryland agro-ecosystems.